Complete mitochondrial genome of yellow-rumped honeyguide Indicator xanthonotus (Piciformes: Indicatoridae) - Yubao Duan; Yuan Li; Dan Liang; Shimiao Shao; Xu Luo (Mitochondrial DNA. Part B. Resources, 2018)
In this study, we first sequenced and described the complete mitochondrial genome and phylogeny of Indicator xanthonotus. The whole genome of I. xanthonotus was 17,603 bp in length and contained 14 protein-coding genes, 22 transfer RNA genes, two ribosome RNA genes, and two non-coding control regions. The overall base composition of the mitochondrial DNA was 31.09% for A, 27.34% for T, 28.96% for C, and 12.61% for G, with a GC content of 41.57%. A phylogenetic tree strongly supported that I. xanthonotus clustered with another Piciformes species by high probability.